2016
DOI: 10.5217/ir.2016.14.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic improvement with gluten restriction in irritable bowel syndrome: a prospective, randomized, double blinded placebo controlled trial

Abstract: Background/AimsThe existence of non-celiac gluten sensitivity has been debated. Indeed, the intestinal and extra-intestinal symptoms of many patients with irritable bowel syndrome (IBS) but without celiac disease or wheat allergy have been shown to improve on a gluten-free diet. Therefore, this study set out to evaluate the effects of gluten on IBS symptoms.MethodsWe performed a double-blind randomized placebo-controlled rechallenge trial in a tertiary care hospital with IBS patients who fulfilled the Rome III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 32 publications
1
42
0
2
Order By: Relevance
“…A prospective open‐label study of 41 patients with IBS with diarrhoea undertaking a GFD demonstrated clinically significant improvements in the IBS symptom severity at 6 weeks; moreover, the vast majority (72%) continued with a GFD long‐term and remained in clinical remission at 18‐month follow‐up . There are also now several RCTs demonstrating the benefits of GFD in IBS , with Table outlining some of the key studies.…”
Section: Gluten‐free Dietmentioning
confidence: 99%
“…A prospective open‐label study of 41 patients with IBS with diarrhoea undertaking a GFD demonstrated clinically significant improvements in the IBS symptom severity at 6 weeks; moreover, the vast majority (72%) continued with a GFD long‐term and remained in clinical remission at 18‐month follow‐up . There are also now several RCTs demonstrating the benefits of GFD in IBS , with Table outlining some of the key studies.…”
Section: Gluten‐free Dietmentioning
confidence: 99%
“…In this regard, such patients resemble those who have irritable bowel syndrome and suggest an overlap between the 2 conditions . Such a concept is supported by a recent study in subjects with irritable bowel syndrome who showed improvement on a GFD and recurrence of symptoms following wheat consumption …”
Section: Nonceliac Gluten Sensitivitymentioning
confidence: 65%
“…Furthermore, a prospective study of a gluten-free diet in diarrhea-predominant IBS patients without celiac disease found that 71% responded well to the intervention, with greater benefit in HLA-DQ2/8-positive subjects [106]. Further supporting a role of NCGS in IBS, gluten re-challenge after a gluten-free diet was found to significantly worsen symptoms within 1 week [107].…”
Section: Non-celiac Gluten Sensitivitymentioning
confidence: 93%